Essays on market power and price strategy in the U.S. dairy industry - Fang, Shengnan (Kansas State University, 2019)
This dissertation constitutes two essays discussing the market power and price strategy in the dairy industry, which historically played an important role in the U.S. agriculture sector. The first essay focuses on a merger case in the dairy industry. On April 1, 2009, Foremost Farms USA (referred to as Foremost Farms), a Wisconsin-based dairy producers’ cooperative, sold its consumer products division, which included two dairy processing plants, to Dean Foods, and these plants produced distinct brands of milk. The United States Department of Justice (DOJ) expressed concern that this acquisition would have substantial anticompetitive effects in certain markets. Consistent with this view, in July 2011, the DOJ issued a final order requesting that Dean Foods divest one of the newly acquired plants. This essay empirically examines whether DOJ’s concern, as well as its policy action, are supported by the data. The results suggest that, except for two package sizes of milk, Dean Foods jointly priced the newly acquired brands of milk along with its pre-existing milk brands, and such cooperative price-setting behavior is consistent with an anticompetitive effect. However, the magnitudes of the percentage increases in price-cost markups due to joint pricing are sufficiently small, suggesting that anticompetitive effects should not be of concern. In case of the divestiture period, we find that a subset of the products from the divested brand went back to being priced separately from Dean Food’s milk products as required by DOJ’s order. However, the magnitudes of the percentage decreases in price-cost markups are sufficiently small, suggesting that divestiture effects are negligible. Consumers’ perception of the marginal quality difference between organic and conventional products allow firms to charge a price premium associated with the perceived quality difference, the organic price premium. The organic price premium is effectively consumers’ willingness to pay (WTP) for the organic attribute. The second essay addresses the question of how the quantity of media coverage on organic dairy issues impacts the organic price premium for milk. We first use a theoretical model to illustrate how media information may influence the organic price premium. Our subsequent empirical analysis suggests, on average, consumers are willing to pay $1.19/gallon more for the organic attribute of milk, which corresponds to 19.07% of the mean price per gallon of organic milk. Second, we find evidence that the quantity of newspaper coverage on organic dairy issues significantly increases WTP for the organic feature of milk, but this impact follows an inverted-U curve with a diminishing marginal effect. Interestingly, TV and Radio news coverage of similar issues are not found to have a significant effect on WTP, which may be partly driven by survey evidence suggesting that consumers’ main reason for listening to radio or watching TV is to be entertained rather than to be informed.
Keywords: Antitrust policy; Price-setting behavior; Dairy industry; Organic price premium; News media coverage